Induced human decidual NK-like cells improve utero-placental perfusion in mice - Cavalli, RC; Cerdeira, AS; Pernicone, E; Korkes, HA; Burke, SD; Rajakumar, A; Thadhani, RI; Roberts, DJ; Bhasin, M; Karumanchi, SA; Kopcow, HD (Public Library of Science, 2016)
Decidual NK (dNK) cells, a distinct type of NK cell, are thought to regulate uterine spiral artery remodeling, a process that allows for increased blood delivery to the fetal-placental unit. Impairment of uterine spiral artery remodeling is associated with decreased placental perfusion, increased uterine artery resistance, and obstetric complications such as preeclampsia and intrauterine growth restriction. Ex vivo manipulation of human peripheral blood NK (pNK) cells by a combination of hypoxia, TGFß-1 and 5-aza-2'-deoxycytidine yields cells with phenotypic and in vitro functional similarities to dNK cells, called idNK cells. Here, gene expression profiling shows that CD56Bright idNK cells derived ex vivo from human pNK cells, and to a lesser extent CD56Dim idNK cells, are enriched in the gene expression signature that distinguishes dNK cells from pNK cells. When injected into immunocompromised pregnant mice with elevated uterine artery resistance, idNK cells homed to the uterus and reduced the uterine artery resistance index, suggesting improved placental perfusion.